A Legal Analysis of the Sale of Sacrificial Animal Skin in the Nahdliyin Tradition: Perspectives from I‘ānat Al-Ṭālibīn and Al-Majmū‘ Syarḥ Al-Muhadzdzab - Muhammad Royyan Faqih Azhary; Abdulazeem Abozaid (Al Wajiz: Journal of Sharia and Economics Studies, 2026)
The ritual of animal sacrifice in Islam carries both spiritual and social significance, yet contemporary practices of selling sacrificial skins have raised legal questions among Muslim communities, particularly within the Nahdliyin tradition in Indonesia. This research examines the legal ruling on selling sacrificial animal skins within the Shafi'i school of Islamic jurisprudence, focusing specifically on two authoritative classical texts, I'ānat Al-Ṭālibīn and Al-Majmū' Syarḥ Al-Muhadzdzab, and their relevance to contemporary societal practices. This study employs a library research method with a descriptive-analytical approach. Primary sources are the two aforementioned fiqh texts, while secondary sources include academic journals, fiqh books, and previous studies. Data analysis was conducted using content analysis to understand scholarly views and their application to modern practices. The findings reveal that the Shafi'i school explicitly prohibits the sale of sacrificial animal skins, as all parts of the sacrificial animal are considered integral to an act of worship and cannot be commercialized. The skin may only be used personally, lent, or given in charity without any buying and selling element. This prohibition also extends to giving the skin to a butcher as payment for slaughtering services. Although other schools, such as the Hanafi, permit selling the skin for social purposes, the Shafi'i school maintains its prohibition as a form of precaution and preservation of the sacrificial ritual's sanctity. This research underscores the importance of educating Muslims on the fiqh of sacrifice to ensure community practices align with Islamic legal principles. It offers sharia-compliant alternatives for managing sacrificial skin and analyzes the implications of the prohibition within contemporary Muslim society.